Nonmetastatic breast cancer patients subsequently developing second primary malignancy: A population‐based study. (13th October 2021) - Bao, Shengnan; Jiang, Mengping; Wang, Xi; Hua, Yijia; Zeng, Tianyu; Yang, Yiqi; Yang, Fan; Yan, Xueqi; Sun, Chunxiao; Yang, Mengzhu; Fu, Ziyi; Huang, Xiang; et al.
Abstract: Background: With life span extending, breast cancer (BC) survivors may face the possibility of developing second primary cancer (SPC) and considerably shorten survivorship. However, little is known about multiple primary cancer (MPC) patients with nonmetastatic breast cancer as a first primary malignancy (BCFPM). Methods: Here, we retrospectively analyzed data on cancer survivors with BCFPM diagnosed between 2010 and 2015 from the Surveillance, Epidemiology, and End Results (SEER) database. The prognostic factors for breast cancer‐specific survival (BCSS) were ascertained by the stepwise regression analysis and a competing risk model, and were integrated to the establishment of prognostic nomogram, of which the accuracy was measured by the calibration curve and the concordance index (C‐index). Results: In total, 8616 patients were identified with 4.6% of 3‐year breast cancer‐ specific death (BCSD) and 8.6% of 5‐year BCSD. The most common SPC among BCFPM patients were female BC and lung cancer. Besides, the median latency time between BC and SPC was 22 months. At a ratio of 7:3, all patients were randomly categorized into a training cohort ( n  = 6032) and a validation cohort ( n  = 2584). By a proportional subdistribution hazards regression analysis, the following factors were considered to own independent prognostic abilities of BCSS: subtypes, grade, T classification, N classification, radiation, and sites of SPC. The nomogram could accurately predict 3‐year and 5‐year breast cancer‐associated survival of BCFPM patients with high internal and external validated C‐index, 0.715 (95% CI, 0.691–0.739), and 0.683 (95% CI, 0.642–0.724), respectively. Conclusions: BC survivors remained a high risk of developing SPC and considerably shortened survival time. In this study, a favorable nomogram was constructed to as a prediction model for 3‐year and 5‐year BCSS of BCFPM patients, largely intending to prolong the life of these patients by assisting clinicians to make individualized follow‐up plans. Abstract : A remarkable number of second primary cancers (SPC) occur in breast cancer survivors and constitute an emerging subgroup of tumors, with a shortage of overall understanding and normative management. Here, we gathered a mass of retrospective data with precise definition of SPC and further explored the clinical characteristics and prognostic predictors of these patients, thus effectively avoiding the deviation caused by small sample and SPC misclassification.